Functional characterization and evolution of olfactory responses in coeloconic sensilla of the global fruit pest Drosophila suzukii - Qi Xue; Kazi Sifat Hasan; Omar Dweck; Shimaa A. M. Ebrahim; Hany K. M. Dweck (BMC Biology, 2025)
Abstract Background When a species changes its host preference, it often requires modifications in its sensory systems. Many of these changes remain largely uninvestigated in the global fruit pest Drosophila suzukii (also known as spotted wing Drosophila, SWD). This species, which shares a last common ancestor with the model organism D. melanogaster—a species that prefers overripe fruits— ~ 15 million years ago, has shifted its preference from overripe to ripe, soft-skinned fruits, causing significant damage to fruit industries worldwide. Results Here, we functionally characterized the coeloconic sensilla in D. suzukii and compared their responses to those of its close relatives, D. biarmipes and D. melanogaster. We find that D. suzukii’s responses are grouped into four functional types. These responses are consistent across sexes and reproductive status. The odorant receptor co-receptor Orco is required for certain responses. Comparative analysis across these species revealed evolutionary changes in physiological and behavioral responses to specific odorants, such as acetic acid, a key indicator of microbial fermentation, and phenylacetaldehyde, an aromatic compound found in a diverse range of fruits. Phenylacetaldehyde produced lower electrophysiological responses in D. suzukii compared to D. melanogaster and elicited strong attraction in D. suzukii but not in any of the other tested species. Conclusions The olfactory changes identified in this study likely play a significant role in the novel behavior of D. suzukii. This work also identifies phenylacetaldehyde as a potent attractant for D. suzukii, which can be used to develop targeted management strategies to mitigate the serious impact of this pest.